Anthropometric History in Chile: Height Evolution of the Population in the Long-Run, Xviii to Xx Centuries - Navarrete-Montalvo, J; Llorca-Jana, M; Araya-Valenzuela, R (UNIV CATOLICA NORTE, 2018)
The average height of a population has been recently taken as a good indicator of biological welfare, and therefore of standards of living and economic development. This article provides the first available series for Chile, providing the evolution of the average height of Chilean soldiers (male) born from the 1730s to the 1980s, using a sample of 6.200 individuals. This sample can be safely taken as a good proxy of the average height of Chilean male population for the period under study. Having analysed our data, our main conclusions are: (i) around mid-eighteenth century the average height of Chileans was rather high if compared to Chile itself, as well as to other countries of the region and Europe; (ii) during the nineteenth century the average height of Chileans declined during a long spell, (iii) in the twentieth century there was an important increase in the average male height, but in the developed world height increased faster than in Chile.